„It’s not on the Poet to Bow to the King”. The Dissident’s Position in Croatian Theatre Studies – the Ivšić Case - Petranović, Martina (Poznańskie Studia Slawistyczne, 2014)
The paper discusses the position of Croatian playwright Radovan Ivšić in Croatian theatre historiography, before and after the independence of Croatia in the nineties. The research results point to three major phases in Ivšić’s reception in Croatian theatre historiography – the rejection, acceptance and canonization.